I couldn't put the other graph but they both the intersected at (5,0)
Answer:
b
Step-by-step explanation:
cause I smart
Answer:
4
Step-by-step explanation:
thz for the point :)))))))))))
Ok so the answer is D because first I solved the equation because you can’t find which answer choice it is equivalent to if you didn’t solve it ... so I solved the equation and got x=-3/2 how I solved this is
3^-x = 3^3x+6 ... since the bases are the same, set the exponents equal
-x=3x+6..... move the variable to the left-hand side and change its side
-x-3x=6 ... collect like terms
-4x = 6..... divide both sides of the equation by -4 and I got x=-3/2
I don’t want this text to be that long so they both seem calculated the same way that’s why i got -3/2 hope that helps;-;
Answer:
-8+5√2 and -8-5√2
Step-by-step explanation:
Given the expression x² + 16x + 14 = 0
USing the general formulas
x = -16±√16²-4(14)/2
x = -16±√256-56/2
x = -16±√200/2
x = -16±10√2/2
x = -8±5√2
Hence the required solutions are -8+5√2 and -8-5√2